Expert opinion on the prescription practice of dual combination oral anti-diabetic drugs in type 2 diabetes mellitus management - S., Manjula; Kumar M. , Krishna (International Journal of Research in Medical Sciences, 2024)
Background: This study aimed to gather the clinicians’ perspective regarding the use and prescription practice of dual combination oral anti-diabetic drugs (OADs) in type 2 diabetes mellitus (T2DM) management in Indian settings. Methods: A cross-sectional study was conducted by using a 29-item structured questionnaire covering factors considered, challenges, preferred indicators of glycemic control, continuous glucose monitoring (CGM) use, and strategies. Additionally, it explored clinicians’ feedback and experiences with dual combination oral anti-diabetic drugs in T2DM management. Results: Seventy percent of clinicians observed improved adherence to dual combination therapy of OAD. The combination of dipeptidyl-peptidase 4 (DPP4) inhibitors and metformin was favored for early initiation and showed better tolerability within the first year according to 42% of clinicians. Approximately 63% of clinicians prefer vildagliptin + metformin for 40–50 year-old diabetics. The combination yields favorable outcomes: 21% in young, 14% in elderly, and 7% in long-standing diabetes cases. After 5 years, 37% of clinicians observed 40-50% of diabetics reaching an HbA1c goal of <7.0% with this combination. Clinicians choose glimepiride + metformin for treatment intensification based on its efficacy, cardiovascular (CV) safety, and fewer adverse events. These factors were collectively recognized by 66.54% of respondents. Conclusions: This study provided valuable insights into real-world clinical practices and preferences regarding dual combination therapy for diabetes management. Clinicians identified the fixed-dose combination of DPP4 inhibitors and metformin as the preferred choice and highlighted the effectiveness of glimepiride + metformin in overcoming treatment intensification challenges.